Alles, was wir nicht erinnern Polen, Deutsche und die Zäsur des 24. Februar ’22 - Hoffmann, Christine (Porównania, 2025)
Alles, was wir nicht erinnern Polen, Deutsche und die Zäsur des 24. Februar ’22